Analisis Kebutuhan E-Modul Fisika sebagai Bahan Ajar Berbasis PBL di MA Muslimat NU - Iva Malina; Hadma Yuliani; Nur Inayah Syar (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2021)
This research was conducted to develop a learning resource of the type of learning media in the form of PBL-based teaching materials. Thus, research requires a preliminary study consisting of literature studies and field studies. The type of research conducted is descriptive qualitative research. The data collection instruments of this research were in the form of interview sheets for teacher needs analysis, and student needs analysis questionnaires. The teaching materials developed are in the form of electronic modules (e-modules) that can contain text, images, and learning videos, as an independent learning effort that is systematically arranged. To create an e-module using the Flip PDF Professional application. Needs analysis was conducted to find out the learning resources used by the teacher, the obstacles during the learning process, and the learning resources needed by the students. The results of the analysis of the needs of 44 students of class XI science obtained that 95.5% had a handbook for studying physics, however, 77.3% of students in the static fluid material in the handbook were difficult to understand. So according to 52.3% of students the handbook used is not sufficient as a learning resource and 95.5% of students need other learning resources to support learning activities and 93.2% of students need other learning resources that can be understood independently. These results indicate the need to develop teaching materials in the form of e-modules based on PBL static fluid materials.